2020
DOI: 10.2147/cia.s272610
|View full text |Cite
|
Sign up to set email alerts
|

<p>Early Postoperative Hypoalbuminaemia as a Risk Factor for Postoperative Pneumonia Following Hip Fracture Surgery</p>

Abstract: Purpose: Postoperative pneumonia is a common and devastating complication of hip fracture surgery in older individuals. This study aimed to determine the relationship between early postoperative hypoalbuminaemia and pneumonia after hip fracture surgery. Patients and Methods: In this retrospective cohort study conducted at one centre, we reviewed the medical records of 1155 consecutive patients (>60 years) who underwent hip fracture surgery. Multivariate logistic regression analysis was performed to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 46 publications
4
29
0
Order By: Relevance
“…POP occurs frequently in patients undergoing hip fracture surgery, particularly in older patients. Results of this meta-analysis revealed that the overall prevalence of POP was 4.8%, which was comparable to the previously reported range of 4.1–15.3% in patients with hip fracture [ 7 9 , 11 ]. POP is closely associated with prolonged hospital stay and significantly increased mortality [ 5 8 ].…”
Section: Discussionsupporting
confidence: 85%
“…POP occurs frequently in patients undergoing hip fracture surgery, particularly in older patients. Results of this meta-analysis revealed that the overall prevalence of POP was 4.8%, which was comparable to the previously reported range of 4.1–15.3% in patients with hip fracture [ 7 9 , 11 ]. POP is closely associated with prolonged hospital stay and significantly increased mortality [ 5 8 ].…”
Section: Discussionsupporting
confidence: 85%
“…2f). However, after sensitivity analysis by eliminating studies published after 2020, the I 2 value for five studies 4,5,8,10,13 decreased to 0%, and the significance remained unchanged ( OR = 2.21, 95% CI : 1.61–3.02, P < 0.0001) (Fig. S1d).…”
Section: Resultsmentioning
confidence: 99%
“…Early surgery is recommended for such patients 2 . Postoperative pneumonia (POP) is the commonest postoperative complication, with an incidence of 3.5%–15.2%, ranking second to delirium 3–13 . Negative outcomes associated with POP included prolonged hospital length of stay, more frequent intensive care unit (ICU) stays, and a higher rate of sepsis, readmission, and mortality 14–16 .…”
Section: Introductionmentioning
confidence: 99%
“…Toshihiro et al 30 investigated 426 elderly patients undergoing surgery for hip fracture and found postoperative hypoalbuminemia was associated with 5.8-fold increased risk of postoperative pneumonia. Shin et al 2 investigated 1,155 elderly patients undergoing surgery for hip fracture and found postoperative hypoalbuminemia was associated with 2.4-fold increased risk of postoperative pneumonia. In their study, multivariate regression analysis was also used, similar to ours and the cut-off value for albumin level was determined as 3.0g/L and 3.5g/L.…”
Section: Discussionmentioning
confidence: 99%